2017
DOI: 10.1093/biosci/biw159
|View full text |Cite
|
Sign up to set email alerts
|

Metaresearch for Evaluating Reproducibility in Ecology and Evolution

Abstract: Recent replication projects in other disciplines have uncovered disturbingly low levels of reproducibility, suggesting that those research literatures may contain unverifiable claims. The conditions contributing to irreproducibility in other disciplines are also present in ecology. These include a large discrepancy between the proportion of “positive” or “significant” results and the average statistical power of empirical research, incomplete reporting of sampling stopping rules and results, journal policies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 63 publications
1
86
0
Order By: Relevance
“…, Leek and Peng , Fidler et al. ). One practice is for authors to share both code and data that generated the specific results shown in their peer‐reviewed publications (Poisot et al.…”
Section: Computational Reproducibilitymentioning
confidence: 99%
“…, Leek and Peng , Fidler et al. ). One practice is for authors to share both code and data that generated the specific results shown in their peer‐reviewed publications (Poisot et al.…”
Section: Computational Reproducibilitymentioning
confidence: 99%
“…In the field of psychology, replication of 100 studies found that replication effects were half the size of original study effects, and only 39% of these effects were judged to have replicated original results (Open Science Collaboration, ). There is growing recognition that reproducibility is likely to be an important problem in ecology as well (Ellison, ; Fidler et al, ; Ives, ; Parker et al, ; Schnitzer & Carson, ). The lead entry in a list of proposals developed by Begley and Ioannidis () to deal with the reproducibility crisis and improve quality of scientific research was for editors to solicit replication bids, rewarding investigators willing to undertake serious efforts at replicating published results (Wagenmakers & Forstmann, ).…”
Section: Motivation: Once Is Not Enoughmentioning
confidence: 99%
“…The biomedical community has devoted substantial attention to this issue, developing several promising approaches for dealing with different sources of study bias, for example (Turner, Spiegelhalter, Smith, & Thompson, ). Nonetheless, the following claim by Ioannidis () is sobering: “Few systematic reviews and meta‐analyses are both non‐misleading and useful.” Recent calls for transparency in reporting ecological research have been directed largely at increasing the utility of published investigations for research summaries and meta‐analyses (Ellison, ; Fidler et al, ; Parker et al, ; Schnitzer & Carson, ). Importantly from the perspective of this essay, the opportunistic nature of most meta‐analyses precludes design of component studies and does not provide natural opportunities for designing sequences of studies.…”
Section: Approaches To Accumulating Evidencementioning
confidence: 99%
“…The response of the EVE community to these calls has ranged 18 from tepid to skeptical (e.g., Ecology Letters Senior Editors 2016, Schnitzer & Carson 2016) for 19 reasons that echo those put forward by scientists in other fields: a lack of incentives or 20 professional rewards for carrying out replications, few journals willing to publish the results of 21 replicated studies, and concerns about efficient use of scarce research funding (Nakagawa & 22 Parker 2015, Schnitzer & Carson 2016, Fidler et al 2017. In addition to these practical 23 obstacles, however, many suggest a more fundamental conceptual obstacle --that research in 24 EVE is inherently impossible to replicate because it is carried out under unique biotic and abiotic 25 conditions (e.g., species composition and abundance, weather conditions, site history).…”
Section: Several Authors Have Suggested That Field-based Sciences Sucmentioning
confidence: 99%